2016
DOI: 10.1080/23262133.2016.1259709
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of IGF-I on hippocampal neurogenesis and function during aging

Abstract: In rats, learning and memory performance decline during normal aging, which is paralleled by a severe reduction of the levels of neurogenesis in the hippocampal dentate gyrus (DG). A promising therapeutic strategy to restore neurogenesis in the hippocampus of old rats and their spatial memory involves the use of insulin-like growth factor-I (IGF-I). The peptide exerts pleiotropic effects in the brain, regulating multiple cellular processes. Thus, 4-week intracerebroventricular (ICV) perfusion of IGF-I signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…Neurodegenerative diseases like Alzheimer's, Parkinson's diseases and prion disorders are associated with aging [88][89][90][91][92]. A number of promising results show that IGF-1 has a restorative impact on the brain by expanding hippocampal neurogenesis and memory accuracy in older people and potentially in individuals with neurodegenerative disorders [93]. IGF-1 has a progressively more powerful trophic impact than GH on sensory and motor neurons and on neuronal growth and recovery.…”
Section: Role Of Igf-1 In Neurodegenerationmentioning
confidence: 99%
“…Neurodegenerative diseases like Alzheimer's, Parkinson's diseases and prion disorders are associated with aging [88][89][90][91][92]. A number of promising results show that IGF-1 has a restorative impact on the brain by expanding hippocampal neurogenesis and memory accuracy in older people and potentially in individuals with neurodegenerative disorders [93]. IGF-1 has a progressively more powerful trophic impact than GH on sensory and motor neurons and on neuronal growth and recovery.…”
Section: Role Of Igf-1 In Neurodegenerationmentioning
confidence: 99%
“…The bioavailability of IGF-1 and IGF-2 and their binding proteins (IGF-BP2 and IGF-BP3) could play an important role in the prevention and treatment of several neurologic disorders [ 49 ]. Emerging promising results demonstrates that IGF-1 possesses a therapeutic effect on the brain by increasing hippocampal neurogenesis and memory accuracy in elderly individuals, and possibly, in neurodegenerative disorders [ 50 ]. Mashayekhi et al [ 51 ] found the serum level of IGF-1 and IGFBPs were higher in patients affected by Parkinson disease compared to controls, but the significance of these data in the pathophysiology of the disease remains unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility exists that GH induced the local expression of IGF-1, as it has been demonstrated in the human fetal cortex [33], but not in human adult brain. In fact, an important role for IGF-1 in neurodegenerative diseases has been postulated long time ago [34], and recently it has been published that IGF-1 increases hippocampal neurogenesis and improves memory in old patients [35]. Even more, it has been postulated that treatment with this peptide might be useful in neurodegenerative diseases, including Alzheimer's disease [36].…”
Section: Discussionmentioning
confidence: 99%